Adoption of recommended quality control practices by fish processing factories - and Kand, Kaul, P.N. and Krishna Iyer, H. (Fishery Technology, 2021)
Responses to mailed questionnaires from 31 fish processing factories revealed that for 55 recommended practices in quality control, the percentage of adopters varied from 21.43 to 100.The adoption index was not correlated to any of five variables studied. The mean adoption index did not differ significantly between five other criteria related to fish processing. Rate of rejection or reprocessing at the factory itself was highly correlated with the amount of water used per tonne of processed material.